(untitled) (Annals of Medical Research, 2023)
Aim: For the treatment of peripheral facial paralysis, the superiority of the use of steroid alone and the use of steroid + antiviral over each other has not been clarified in the literature. In this study, the efficacy of using steroid treatment alone and using a combination of steroid+antiviral treatment in patients we followed up with peripheral facial paralysis in our clinic was questioned retrospectively. It was aimed to clarify the efficacy and superiority of steroid alone and steroid+antiviral therapy in patients with peripheral facial paralysis. Materials and Methods: One hundred and ten patients who received only steroids and 62 patients who received combination therapy were included in the study. Age, gender, regular drug use, smoking, previous history of facial paralysis, comorbid diseases, initial stage of the disease (House-Brackman/HB staging), treatment protocol and response to treatment were recorded from the files examined. Patients with HB stage ≤2 at the 6th month follow-up were considered to have responded well or completely to the treatment. Results: When the group receiving only steroid treatment and the group receiving steroid + antiviral treatment were compared in terms of age, chronic drug use, gender, and previous facial paralysis, no statistically significant difference was observed. The groups were compared in terms of response to treatment, 88.2% improvement was observed in the steroid group (HB stage ≤2), and 91.9% improvement was observed in the combined treatment group. No statistically significant difference was observed (p=0.605). Conclusion: For the treatment of peripheral facial paralysis, the superiority of steroid use alone and combined antiviral + steroid use has not been proven. In the light of the literature, it is recommended that the patient be treated with steroids at the earliest stage.